Relationship Between Triglyceride Tolerance, Body Mass Index, and Fat Depots in Hospitalized Patients Receiving Parenteral Nutrition. (November 2015) - Frazee, Erin N.; Nystrom, Erin M.; McMahon, M. Molly; Williamson, Eric E.; Miles, John M.
Background: Hypertriglyceridemia has been associated with adverse outcomes in patients receiving intravenous fat emulsions (IVFEs), but little is known about its prevalence and causes. Materials and Methods : The study investigated whether a relationship exists between body mass index (BMI) and triglyceride tolerance in parenterally fed patients. We conducted a retrospective analysis of 287 adults receiving parenteral nutrition to determine whether patients with very low BMI (VLBMI, <16 kg/m 2 ) tolerate IVFEs better than do patients with low BMI (LBMI, 16–18.4 kg/m 2 ), normal-weight patients (NBMI, 18.5–24.9 kg/m 2 ), and overweight/obese patients (HBMI, ≥25 kg/m 2 ). Results : The median triglyceride concentration during IVFE was significantly lower in VLBMI patients at 107 mg/dL compared with 124 mg/dL in non-VLBMI patients ( P = .016), despite higher lipid infusion rates in the VLBMI group. There was a significant association between triglycerides and BMI in the aggregate cohort ( R = 0.2375, P < .0001), with the highest frequency of hypertriglyceridemia occurring in HBMI patients despite relatively lower lipid and energy supply. In a subset of VLBMI patients (n = 36) who had an abdominal computed tomography scan, there was 25- to 100-fold variability in the size of the abdominal adipose tissue depots. In this subgroup, triglyceride concentrations correlated with visceral fat but not subcutaneous abdominal fat. Conclusions : In summary, patients with VLBMI have lower triglyceride concentrations during IVFEs than do other individuals, but there is considerable variability in triglycerides and body fat in this group. Caution should be employed with the use of IVFEs, especially in HBMI patients.